Was bringt die Föderalismusreform? Wahrscheinliche Effekte der geänderten Zustimmungspflicht - Simone Burkhart; Philip Manow (Max Planck Institute for the Study of Societies, 2006)
The recently enacted reform of German federalism is supposed to make legislation faster, more efficient and better. To what extent are these expectations justified? In order to assess the likely effects of the reform, this study uses a research design that was recently applied by the Research and Reference Services of the German Bundestag (parliament): we estimate the future effects of the reform by analyzing the impact it would have had on the legislation in the 14th and 15th term of the Bundestag if it had already been been in force at that time. In particular we ask: To what extent would the number of laws requiring the consent of the states' chamber, the Bundesrat, have been reduced? Which type of laws would have been affected by this reduction - the more controversial ones, or the less controversial ones? Which policy sectors would have seen the greatest reduction? How much would the reduction have increased the government's capacity to act effectively? Would the legislative process have been accelerated? – – Die verabschiedete Föderalismusreform soll die Gesetzgebung in Deutschland schneller, effizienter und besser machen. Inwiefern sind diese Erwartungen berechtigt? Zur Abschätzung der Reformfolgen auf die Bundesgesetzgebung folgen wir in dem vorliegenden Working Paper einer Vorgehensweise, die der Wissenschaftliche Dienst des Bundestages kürzlich in einer Studie angewandt hat: Die Auswirkungen der Föderalismusreform insbesondere auf die Zustimmungspflicht werden anhand der Gesetzgebung der 14. und 15. Legislaturperiode untersucht. Wir fragen insbesondere: Wie stark hätte sich der Anteil der Zustimmungsgesetze verringert, wenn die neuen Zustimmungsregeln schon in diesen beiden Legislaturperioden gegolten hätten? Wären eher zwischen Regierung strittige oder unstrittige Gesetze von der Zustimmungspflicht befreit worden? Welche Politikbereiche wären betroffen? Wie sehr hätte sich die politische Handlungsfreiheit der Bundesregierung erhöht? Wäre die Gesetzgebung durch die veränderten Zustimmungsregeln beschleunigt worden?
Keywords: 300